The effectiveness of using quizizz to improve the achievement of indonesian language learning outcomes on synonyms and antonyms material in grade 5 elementary school students - Hariyastuti, Anik; Triana, Vivit (Universitas Nusantara PGRI Kediri, 2024)
The challenges of education have become more difficult over time. Some of these challenges include the fact that teachers/educators try to help students understand the lessons at hand, but often the results are not as expected. Students find it difficult to concentrate and understand the abstract concepts of their lessons. To deal with this problem, applications and other game systems are used that help children to understand the material. In this study, the learning system was carried out by testing the use of Quzizz material as a teaching aid with the object of the experimental class and control class, namely 5th-grade students from SD Negeri Bedug 01, Pangkah, Tegal. The results showed that Quzizz helped teaching with language materials (antonyms and synonyms), besides that students enjoyed the learning process more. This is because students do not feel pressure to learn and enjoy the learning process as a fun process for them